ROH KUDUS SEBAGAI “METERAI－JAMINAN” DALAM EFESUS 1:13-14 SERTA IMPLIKASINYA BAGI SOTERIOLOGI KRISTEN - Bruno Ikun Anen; Mozes Lawalata (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2026)
The Holy Spirit is a divine person who plays a vital role in all biblical evidence. Since creation, the Spirit of God has been present and actively working in shaping and sustaining creation according to God's will (Genesis 1:2). In the Old Testament, the Spirit of God empowered judges, prophets, and the chosen people to carry out their duties in the plan of salvation, while also providing the basis for the eschatological hope of the renewal of humanity through the outpouring of the Spirit. In the New Testament, the work of the Holy Spirit is increasingly evident through the life and ministry of Jesus Christ, from his birth and baptism to his ministry as the fulfillment of messianic prophecy. In Pauline theology, the Holy Spirit is the core experience of salvation because through the Spirit believers are renewed, freed from the power of sin, and live in fellowship with God. Ephesians 1:13–14 is a key text that affirms that believers are "sealed" with the Holy Spirit, and that the Spirit serves as a "guarantee" of their inheritance of salvation. The term "seal" refers to divine ownership, approval, and protection, while "guarantee" implies an initial payment that guarantees the fulfillment of salvation in the future. However, in contemporary church practice, the meaning of the Holy Spirit as a seal and guarantee is often understood in a limited way, only as a sign of the believer's identity, so that the eschatological dimension and the certainty of salvation are less considered. Therefore, this study examines Ephesians 1:13–14 through a qualitative method with a grammatical-historical exegetical approach within a canonical hermeneutic framework. The results show that the Holy Spirit is a sign of God's ownership of His people as well as a definite guarantee of the perfect fulfillment of salvation in the future. Keywords: Holy Spirit, Seal, Guarantee, Ephesians 1:13–14, Certainty of Salvation, Pneumatology, Soteriology.